HPTLC PROFILE OF QUERCETIN IN THREE CULTIVARS OF Allium cepa AND ITS ANTIMICROBIAL ACTIVITY AGAINST BACTERIAL CULTURES - Lekshmi NCJ, Packia; S, Viveka; Mb, Viswanathan; Mini Shobi T; JEEVA S; RAJA BRINDHA J (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: This study was subjected to analyse the technique for the determination of quercetin, a flavonoid in onion (Allium cepa L.) from three different cultivars of bulb onion (O1, O2 and O3) which were extracted with petroleum ether, chloroform, methanol and water. Also this study was aimed to determine the antimicrobial activity of four solvent extracts of three onion cultivars against ten MTCC bacterial pathogens. Methods: Quercetin in onion was determined by analytical technique, HPTLC and the antimicrobial activity was performed by well diffusion method. Result: Quercetin was determined in all the three cultivars with Rf value 0.68.Â Quercetin was also extracted in all the four solvent extracts of onion cultivars. Apart from quercetin, few more compounds also isolated.Â More compounds were isolated in O3. In the determination of antimicrobial activity of onion extracts against MTCC cultures revealed that all the three onion cultivars were highly active against Staphylococcus aureus, it showed more than 25mm zone of inhibition.Â Among the three onion cultivars, O2 showed better antimicrobial activity against all the tested bacterial cultures.Â Conclusion: This study showed that onion has good broad spectrum bioactivity against microorganisms revealed that it contains phytochemicals which can be used as neutraceuticals. Keywords: Phytochemicals, High-performance thin layer chromatography, Onion, Quercetin, Antimicrobial activity, Microbial type culture collection cultures.